Difficulties of teaching mathematics courses for the primary stage through the Madrasati platform from the point of view of female teachers in Al- Makhwah Governorate in the Kingdom of Saudi Arabia for the academic year 1443 AH - Alomari, Sharefa Abdulaziz (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the difficulties faced by mathematics teachers in the primary stage before, during and after the class through the Madrasati platform in the Kingdom of Saudi Arabia. The researcher used the descriptive survey method, and the questionnaire was used as a tool for the study. The study population consisted of all primary school mathematics female teachers in Al- Makhwah Governorate, and the sample was chosen by a simple random method, the number of which was 66 female teachers. The researcher reached a number of results:- There are no difficulties before the lesson through the Madrasati platform, the reason is that the platform is characterized by ease of login and use to prepare and prepare lessons and others, with an average of 1.63.- There are some difficulties during the class through the Madrasati platform, with an average of 2.93, the most prominent of which was the difficulty of ensuring that the student understood the lesson, as well as the difficulty of providing the opportunity for all female students to participate during the class through the Madrasati platform. - There are difficulties after the lesson in my school platform, with an average of 3.82 represented in the difficulty of making sure that the student solves the homework or test on her own and without the intervention of a family member.The teachers presented a number of solutions, including: to increase the time allocated to the lesson on the Madrasati platform, and to review the course content by specialists. In addition, the Ministry of Education provides educational applications in a free and secure way to download through the Madrasati platform.
Keywords: My school platform; distance education; mathematics